Comparative Proteomics Reveals the Anaerobic Lifestyle of Meat-Spoiling Pseudomonas Species - Kolbeck, Sandra; Abele, Miriam; Hilgarth, Maik; Vogel, Rudi F. (Frontiers in Microbiology, 2021)
The ability of certain Pseudomonas (P.) species to grow or persist in anoxic habitats by either denitrification, acetate fermentation or arginine fermentation has been described in several studies as a special property. Previously, we had isolated strains belonging to the species P. lundensis, P. weihenstephanensis and P. fragi from anoxic MAP minced beef and further proved their anaerobic growth in vitro on agar plates. This follow-up study investigated the anaerobic growth of two strains per respective species in situ on inoculated chicken breast fillet under 100% N2 modified atmosphere. We were able to prove anaerobic growth of all six strains on chicken breast fillet with cell division rates of 0.2-0.8 /day. Furthermore, we characterized the anaerobic metabolic lifestyle of these Pseudomonas strains by comparative proteomics, upon their cultivation in meat simulation media, which were constantly gassed with either air or 100% N2 atmospheres. From these proteomic predictions, and respective complementation by physiological experiments, we conclude that the Pseudomonas strains P. fragi, P. weihenstephanensis, P. lundensis exhibit a similar anaerobic lifestyle and employ arginine fermentation via the arginine deiminase (ADI) pathway to grow anaerobically also on MAP meats. Furthermore, glucose fermentation to ethanol via the ED-pathway is predicted to enable long term survival but no true growth, while respiratory growth with nitrate as alternative electron acceptor or glucose fermentation to acetate could be excluded due to absence of essential genes. The citric acid cycle is partially bypassed by the glyoxylate shunt, functioning as the gluconeogenetic route without production of NADH2 under carbon limiting conditions as e.g. in packaged meats. Triggered by an altered redox balance, we also detected upregulation of enzymes involved in protein folding as well as disulphide bonds isomerization under anoxic conditions as a counteracting mechanism to reduce protein misfolding. Hence, this study reveals the mechanisms enabling anaerobic grow and persistence of common meat-spoiling Pseudomonas species, and further complements the hitherto limited knowledge of the anaerobic lifestyle of Pseudomonas species in general.